Racism and anti-racism today : principles, policies and practices - Elias, Amanuel (Emerald Publishing Limited, 2024)
Acknowledging efforts to dismantle racism at multiple levels, Racism and Anti-Racism Today examines racism and anti-racism as interconnected rather than isolated issues and proposes a framework for effective anti-racist policy and practice. Providing a unique side-by-side view on current conceptualizations, debates, and policy-praxis, the ten thematic chapters examine the impact of race, racism, and intersecting inequities on contemporary society. They highlight the enduring significance of racial identity politics in shaping social divisions. Engaging in interdisciplinary theoretical debates, Amanuel Elias's scholarship adopts a comparative perspective, incorporating research findings and examples from different geographic contexts. Offering policy recommendations and directions for further research, he contends with fundamental questions that continue to plague the study of racism and its social and economic impact. Why does racism continue to exist and affect societies today despite apparent progress in the acquisition of knowledge, digital connectedness, and human rights discourse? What challenges across societies are blocking efforts to racial equity? What promising anti-racism policy-praxis can we envisage for tackling the impact of racial inequity? Drawing on over a decade of interdisciplinary research, Racism and Anti-Racism Today provides cutting-edge discussion about the present relevance of prejudice to envision an anti-racist future.
Keywords: Racism.; Race relations.; Equality.; Anti-racism -- Social aspects.; Social Science, Race & Ethnic Relations.; Racism and racial discrimination, Anti-racism.; Ethnic groups and multicultural studies.; elektronické knihy; electronic books